2010
DOI: 10.1002/ptr.3106
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural characterization of four endemic Stachys taxa

Abstract: We performed a basic behavioral characterization of methanol extracts of four Balkan endemic Stachys taxa: S. anisochila (SA), S. beckeana (SB), S. plumosa (SP) and S. alpina subsp. dinarica (SAD). The behavioral activity of extracts dosed intraperitoneally in the range 100-400 mg/kg was examined in adult male Wistar rats, in the elevated plus maze, spontaneous locomotor activity, and grip strength tests, mainly predictive of anxiolytic, sedative and myorelaxant actions, respectively. All investigated Stachys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, it is suggested that apigenin has a clear anxiolytic-like effect in mice, without evidencing sedation or muscle relaxation effects. This effect could be mediated by the action of GABA receptor complex [ 40 ]. In agreement with these reports, our high-apigenin containing aqueous extract has increased anxiolytic-like behavior and exploratory activity in 6-OHDA-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is suggested that apigenin has a clear anxiolytic-like effect in mice, without evidencing sedation or muscle relaxation effects. This effect could be mediated by the action of GABA receptor complex [ 40 ]. In agreement with these reports, our high-apigenin containing aqueous extract has increased anxiolytic-like behavior and exploratory activity in 6-OHDA-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids and glycosides with other substances like germacrene, stachysoosides E-H, pinene, iridoid glycoside and stachyssaponin were found in the extracts of Stachys species according to GC-MS analyzing method (Lenherr et al 1984;Sajjadi and Amiri 2007;Ahmad et al 2008;Murata et al 2008;Giuliani et al 2009;Ozturk et al 2009). In addition, there are a lot of substances specified to Stachys species such as chlorogenic asit, phenidon, naphthalene, betulinic-acid, D-camphor, delphinidin, hyperoside, manganese, oleanolic acid, rosmarinic acid, urcolic acid, apigenin and tannin (Delazar et al 2005;Ivanova et al 2009;Savic et al 2010). However, the contents of Stachys petrokosmos leaf extract are not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Sp is endemic in Turkey and it is a 5-10 cm long plant with bushes, flowering at spring and lives at 900-1,100 m, in rocky places of Turkey. The members of the Stachys genus have been used as a medicine for centuries because it contains useful substances such as alpha-and beta-phellandrene, elemol, betulinic acid, D-camphor, delphinidin, hyperoside, saponins, tannins, manganese, urcolic acid, apigenin, rosmarinic acid, oleanolic acid, chlorogenic acid, phenidon, naphthalene and Lavandulifolioside B (Delazar et al 2005;Ivanova et al 2009;Savic et al 2010;Ali et al 2010;Delazar et al 2011). In addition, there are a lot of reports on substances characterized by GC-MS such as phenol, flavonoids, germacrene, stachysosides E-H, alpha and beta-pinene, iridoid glycoside and stachyssaponin which are specific to the Stachy genus (Lenherr et al 1984;Sajjadi and Amiri 2007;Ahmad et al 2008;Murata et al 2008;Giuliani et al 2009;Ozturk et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…S. alpine subsp. dinarica turned out to be the most promising for the preparation of a sedative drug [178].…”
Section: Genus Stachys Lmentioning
confidence: 99%